IDENTIFIKASI KEDALAMAN BERPIKIR REFLEKTIF CALON GURU MATEMATIKA DALAM PEMECAHAN MASALAH MATEMATIKA MELALUI TAKSONOMI BERPIKIR REFLEKTIF BERDASARKAN GAYA KOGNITIF - Syamsuddin, Agustan (Jurnal Elemen, 2020)
Reflective thinking in solving mathematical problems allows students to carry out a reinterpretation process in which cognitive activity involves analytical and decision-making activities on what has been done before. Thus students can realize and think about what he has done and use these skills in subsequent problem-solving. The purpose of this study was to identify the depth of reflective thinking of prospective teachers in solving mathematical problems in terms of differences in cognitive styles. To identify the depth of reflective thinking in problem-solving, using the taxonomic level of reflective thinking consists of six levels, namely (1) remembering, (2) understanding, (3) applying, (4) analyzing, (5) evaluating and (6) creating. This research is a descriptive study with a qualitative approach involving two prospective mathematics teacher students who have a field-dependent cognitive style (SFD) and an independent field (SFI). The results showed that SFD could only reach at three levels, namely remembering, understanding, and applying. While SFI fulfilled the six characteristics of the taxonomic level of reflective thinking, namely remembering, understanding, applying, analyzing, evaluating, and creating.